1999
DOI: 10.1016/s0550-3213(99)00056-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical aspects of large-N reduced models

Abstract: We study the large N reduced model of D-dimensional Yang-Mills theory with special attention to dynamical aspects related to the eigenvalues of the N × N matrices, which correspond to the space-time coordinates in the IIB matrix model. We first put an upper bound on the extent of space time by perturbative arguments. We perform a Monte Carlo simulation and show that the upper bound is actually saturated. The relation of our result to the SSB of the U(1) D symmetry in the Eguchi-Kawai model is clarified. We def… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
278
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 135 publications
(307 citation statements)
references
References 18 publications
(46 reference statements)
28
278
1
Order By: Relevance
“…The results can be fitted to C 6 + C 7 N −2 as one can see from figure 3. This large-N behavior is analogous to the one observed in the bosonic IKKT model [24]. Thus we can obtain the final result for the matrix QM (2.1).…”
Section: Monte Carlo Simulationsupporting
confidence: 80%
See 2 more Smart Citations
“…The results can be fitted to C 6 + C 7 N −2 as one can see from figure 3. This large-N behavior is analogous to the one observed in the bosonic IKKT model [24]. Thus we can obtain the final result for the matrix QM (2.1).…”
Section: Monte Carlo Simulationsupporting
confidence: 80%
“…JHEP09 (2005) Monte Carlo simulation of the models (3.1) and (2.2) can be performed by the heat bath algorithm [24]. For the cQEK model, we first take an average over the ensemble {X i } with the action (2.2) for each Ω, and then perform the averaging over Ω by using random numbers distributed uniformly within the region [− Λ 2 , Λ 2 ].…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…results with those for the corresponding bosonic theory [11], revealed that supersymmetry indeed plays an important role in the dynamics of large-N reduced models as a nonperturbative definition of string theories. Unfortunately, such a direct approach does not work in the IIB matrix model as it stands, due to the fact that the effective action induced by fermions is generically complex, whereas in the above mentioned four-dimensional version, it is real.…”
mentioning
confidence: 80%
“…It has been recognized from those works that the fermionic part of the action plays a crucial role [5,6,7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%